2019
DOI: 10.1017/jfm.2019.161
|View full text |Cite
|
Sign up to set email alerts
|

Capillary waves control the ejection of bubble bursting jets

Abstract: Here we provide a theoretical framework describing the generation of the fast jet ejected vertically out of a liquid when a bubble, resting on a liquid–gas interface, bursts. The self-consistent physical mechanism presented here explains the emergence of the liquid jet as a consequence of the collapse of the gas cavity driven by the low capillary pressures that appear suddenly around its base when the cap, the thin film separating the bubble from the ambient gas, pinches. The resulting pressure gradient deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
159
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(187 citation statements)
references
References 35 publications
27
159
1
Order By: Relevance
“…(2002)). A predictive model of jetting recently proposed in Gordillo & Rodríguez-Rodríguez (2019) and validated through direct numerical simulations in Blanco-Rodríguez & Gordillo (2020) supports this conclusion, where the jet velocity increases as before reaching a peak at a critical and subsequently decreasing as . These interesting predictions need to be tested on the jets reported here using a nonlinear viscous IVP solution.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…(2002)). A predictive model of jetting recently proposed in Gordillo & Rodríguez-Rodríguez (2019) and validated through direct numerical simulations in Blanco-Rodríguez & Gordillo (2020) supports this conclusion, where the jet velocity increases as before reaching a peak at a critical and subsequently decreasing as . These interesting predictions need to be tested on the jets reported here using a nonlinear viscous IVP solution.…”
Section: Discussionsupporting
confidence: 64%
“…It was first shown by Duchemin et al (2002) that the jet velocity has a non-monotonic dependence on viscosity, increasing initially with increasing viscosity but showing a peak at a critical value of viscosity (see figure 12 in Duchemin et al (2002)). A predictive model of jetting recently proposed in Gordillo & Rodríguez-Rodríguez (2019) and validated through direct numerical simulations in Blanco-Rodríguez & Gordillo (2020) supports this conclusion, where the jet velocity increases as Oh 1/2 before reaching a peak at a critical Oh c and subsequently decreasing as Oh −1 . These interesting predictions need to be tested on the jets reported here using a nonlinear viscous IVP solution.…”
Section: Discussionmentioning
confidence: 61%
“…This is an order of magnitude faster than predicted for the bursting bubbles (Deike et al. 2018; Gañán-Calvo 2018; Gordillo & Rodríguez-Rodríguez 2019). The jet diameters of are also two orders of magnitude thinner than those predicted by the bursting-bubble theory (Gañán-Calvo 2018), see also the Comment of Gordillo & Rodríguez-Rodríguez (2018), who question the underlying scaling of this theory.…”
Section: Discussionmentioning
confidence: 58%
“…What is the role of capillary waves in setting up the dimple for the inertial focusing? For the singular jets the dimple dynamics has until recently been formulated in the self-similar capillary-inertial formalism (Zeff et al 2000;Duchemin et al 2002;, while the final cylindrical collapse has most recently been shown to follow pure inertial focusing (Thoroddsen et al 2018;Gordillo & Rodríguez-Rodríguez 2019). One can therefore expect a dynamical transition in the vicinity of the final jet formation.…”
Section: Cross-overmentioning
confidence: 99%
“…The formed liquid jet and the surface waves accelerates the departure of the mother bubble and the next coalescence, leading to more microbubbles being generated in one father‐bubble cycle. The formation mechanism of the fast liquid jet has been investigated and explained in previous studies of bubble bursting at a flat gas–liquid interface, represented by the coalescence of a bubble with an infinitely large bubble (flat interface) 27‐29 . The sudden change in capillary pressure inside the bubble just after coalescence or bursting deforms its base to adopt a truncated cone shape, as shown in Figure 3c at t = 0.25 ms. As the convergence of the last capillary wave, the liquid flow in the vicinity of the cone induces the fast jet after the generation of microbubble, as shown in Figure 3c at t = 0.45 ms.…”
Section: Resultsmentioning
confidence: 94%